Current research status on HER2 protein expression levels and the efficacy of targeted therapy in breast cancer - Liu, Jiani; Peng, Xinyu; Yang, Yang; Yue, Ruixue; Huang, Xuhui; Du, Yongtao; Hu, Chongzhu (Frontiers in Oncology, 2025)
This review summarizes the relationship between HER2 protein expression and the efficacy of three anti-HER2 targeted therapies in breast cancer patients: monoclonal antibodies, antibody-drug conjugates (ADCs), and tyrosine kinase inhibitors (TKIs). The effectiveness of monoclonal antibody therapies positively correlates with HER2 protein expression levels, with HER2 IHC 3+ patients exhibiting better outcomes than IHC 2+/FISH+ patients. In contrast, those with low HER2 protein expression (IHC 1+ or 2+/FISH–) were not beneficial. In patients with HER2-positive breast cancer, the efficacy of T-DM1 is independent of HER2 protein expression levels. Patients with different HER2 expression levels can benefit from T-DXd treatment, with a potential positive correlation with HER2 expression levels. For TKIs, efficacy appeared to be positively correlated with HER2 expression, with HER2 IHC 3+ patients outperforming those with HER2 IHC 1+ or 2+/ISH+. However, high-level evidence to evaluate the relationship between HER2 expression levels and the efficacy of different targeted therapies is lacking. Determining whether HER2 protein expression levels influence treatment outcomes and whether tailored strategies based on HER2 protein expression levels should be implemented holds significant implications for advancing precision medicine in breast cancer.